A Case of Pancreatic Cancer in the Setting of Autoimmune Pancreatitis with Nondiagnostic Serum Markers. (28th May 2013) - Chandrasegaram, Manju D.; Chiam, Su C.; Nguyen, Nam Q.; Ruszkiewicz, Andrew; Chung, Adrian; Neo, Eu L.; Chen, John W.; Worthley, Christopher S.; Brooke-Smith, Mark E.
Abstract : Background . Autoimmune pancreatitis (AIP) often mimics pancreatic cancer. The diagnosis of both conditions is difficult preoperatively let alone when they coexist. Several reports have been published describing pancreatic cancer in the setting of AIP. Case Report . The case of a 53-year-old man who presented with abdominal pain, jaundice, and radiological features of autoimmune pancreatitis, with a "sausage-shaped" pancreas and bulky pancreatic head with portal vein impingement, is presented. He had a normal serum IgG4 and only mildly elevated Ca-19.9. Initial endoscopic ultrasound-(EUS-) guided fine-needle aspiration (FNA) of the pancreas revealed an inflammatory sclerosing process only. A repeat EUS guided biopsy following biliary decompression demonstrated both malignancy and features of autoimmune pancreatitis. At laparotomy, a uniformly hard, bulky pancreas was found with no sonographically definable mass. A total pancreatectomy with portal vein resection and reconstruction was performed. Histology revealed adenosquamous carcinoma of the pancreatic head and autoimmune pancreatitis and squamous metaplasia in the remaining pancreas. Conclusion . This case highlights the diagnostic and management difficulties in a patient with pancreatic cancer in the setting of serum IgG4-negative, Type 2 AIP.